(untitled) (Research, Society and Development, 2020)
The main objective of this study is to trace the profile of students at the Universidade Federal do Ceará (UFC) Medical School, Campus Sobral in relation to study habits and participation in curricular and complementary activities. Data collection occurred between September and October 2019, through the application of a questionnaire with twelve questions on varied topics, such as general information, study methods used and participation in complementary and parallel activities. The data obtained were duly tabulated, resulting in graphs and tables analyzed using descriptive statistics. The analysis of the 264 respondent students indicated that most students are male and, on average, 22 years old. These students use the internet as the main source of study, mainly seeking access to textbooks. About 56% of the students reported difficulties in adapting to academic life, due to the total volume of content and inadequate study methods. The most frequent complementary activity was participation in academic leagues. The theme “Radiology” was considered the main deficiency in the curriculum, being cited by 29.03% of the participants. The parallel activities most performed by the students include cultural events, sports activities, and religious practices. From the topics analyzed in this study, it is possible to observe and understand the reality of the students. This fact is fundamental for the elaboration of more appropriate educational models, aiming at an approach that provides improvements in current medical education.